Innovation and Trade Performance in the United Kingdom. - Greenhalgh, C (1990)
A popular explanation for the U.K.'s poor trade performance in the postwar period is that insufficient attention was paid to the quality of goods offered to consumers. The authors explore the role of both price and quality factors in determining the net trade balances of a number of U.K. manufacturing and service industries. Particular attention is paid to the role of innovation, used empirically as a proxy for product improvement. The findings show considerable support for the view that an advanced industrial country like Britain needs to continually upgrade its products to avoid erosion of its domestic and international market shares.